Students’ Difficulties in Writing English (A Study at The Third Semester Students of English Education Program At University of Bengkulu Academic Year 2011-2012) - Kristy Dwi Pratiwi (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2016)
The title of this study was “Students Difficulties in Writing English”, which was aimed at knowing the students’ difficulties in writing English at third semester students. The population of this research was the whole students at third semester in University of Bengkulu, they were 79 students. All of them are taken as a sample of this research. The data of this research were obtained by using the test of writing a composition, which was scored by using ESL Composition Profile suggested by Jacobs, ET all (1981). Writing difficulties at the third semester varied in the result of the students’ score. The writing difficulty related to the linguistics difficulty (language use and vocabulary aspects) was most difficult one compare to the Cognitive Difficulty (organization and mechanics aspects) and Physiology Difficulty (content aspect) as well.u